Pendidikan Seks Anak di Lingkungan Sekolah : Tindakan Pencegahan Terhadap Tindak Kekerasan dan Pelecehan Seksual - Lidia Agnesia Lumban Batu; Escanna Kabeakan; Cut Kumala Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Sexual harassment and violence against children in the school environment are increasingly concerning issues that require serious handling and prevention strategies. Strategically, sex education can be provided early to teach children about their bodies, their boundaries, and how to find and report inappropriate actions. The purpose of this study was to investigate how sex education functions as a way to prevent violence and sexual harassment in schools. The method used was to conduct literature research on a number of relevant scientific articles that focused Sex education, prevention of sexual violence, sexual harassment, child protection.on the implementation, techniques, and roles of educators and parents. The results showed that age-appropriate sex education provided through visual media, songs, interactive books, and digital applications effectively increased children's understanding of self-protection. The active involvement of parents and teachers also played an important role in the success of this program. This study suggests that sex education should be included in the elementary school curriculum.